Analisis Faktor - Faktor Yang Mempengaruhi Ekspor Common Resource Studi Kasus Ikan Indonesia - Dwipayana, Dewa Made; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
Indonesia is an archipelagic state, the most territory is ocean. Indonesia has good sea potential, from the Indonesian fishery sector has an export value of $ 60,555,064 in 2012. The fish is one commodity that is good for development. Fish has become one of the staple food source of the world community. High protein content and rich in Omega3 good for brain development make very attractive fish communities throughout the world. The purpose of this study was to determine the comparative advantage that Indonesia, Malaysia, Thailand, and Australia, to determine the effect of the US dollar exchange rate, world price, free trade and exports to the neighboring country of export fish in Indonesia, and to know the value of fish exports Indonesia eight years. Data used in this research is secondary data with time series data from 1989 to 2012. The analysis technique used is the VAR  Analasis results showed that variables negatively affect the US dollar exchange rate, variable world price, free trade positive and significant impact on exports. Indonesia has a comparative advantage over Malaysia and Australia.
Keywords: Indonesian fish; International Trade; Export; Exchange Rate; World Price; Free Trade